2019
DOI: 10.1111/jppi.12321
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Education, Training, and Employment Supports for Prisoners With Cognitive Disability: Insights from an Australian Programme

Abstract: The provision of appropriate education, training, and employment supports for incarcerated people is pivotal to mitigating the risk of recidivism, to improving rehabilitative outcomes, and to securing employment upon release. People with cognitive disability are disproportionately represented in prisons internationally. The vast majority of this group have significantly low levels of education, are unable to participate meaningfully in mainstream prison programs, are more likely to return to prison than their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Materials were sometimes simplified to meet the perceived ability of people with disability rather than being specifically designed for them. This reflects findings of previous Australian research showing there are very few specialised education, training or education programmes for people with disability, an issue that must be rectified to reduce the risk of recidivism and improve rehabilitative outcomes (Rowe et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Materials were sometimes simplified to meet the perceived ability of people with disability rather than being specifically designed for them. This reflects findings of previous Australian research showing there are very few specialised education, training or education programmes for people with disability, an issue that must be rectified to reduce the risk of recidivism and improve rehabilitative outcomes (Rowe et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…Other research has highlighted, however, that disability-specific prison units may result in people with disability spending most or all of their sentence within a high-security environment and unable to progress to a lower security rating or facility (Glaser and Deane, 1999). Deferring primary responsibility for prisoners with disability to staff in disability-specific units may also decrease the capacity of mainstream corrections staff to respond to the needs of people with disability (Rowe et al, 2020). Some scholars are also critical of the ability for carceral environments to integrate therapeutic principles, noting that the primary function of prisons to confine individuals against their will necessarily perverts any attempt to incorporate more therapeutic functions (Carlen and Tombs, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Over and above this, some US states had developed special facilities offering pre-release programmes for older prisoners (Davies, 2011), whilst the RELIEF project in Canada delivered training in self-sufficiency and basic living skills to older, frail, conditionally released prisoners in a home-like centre (Davies, 2011). In Australia the 'Future Beyond the Wall' project developed a similar prerelease unit for prisoners with intellectual or cognitive impairment with a focus on functional rather than formal instruction (Rowe et al, 2020). Various arrangements were also described for the pre-term (compassionate) release of prisoners with special care needs, including people who were terminally ill/in need of institutional long-term care (Cornish et al, 2016;Di Lorito et al, 2018;Ethridge & White, 2015;Gibson & Ferrini, 2014;House of Commons Justice Committee, 2020).…”
Section: Early Release Planning/continuity Of Carementioning
confidence: 99%
“…Recent Australian research has identified several elements of effective employment and job skill programmes for people involved with the criminal justice system. These include flexibility and tailoring programmes to individual needs, focusing on strengths and relationships, multi‐pronged and wrap‐around approaches, continuity of support from pre‐ to post‐release, and connecting jobseekers to employers willing to employ them (including securing jobs before release) (Baldry et al, 2018; Graffam et al, 2014a; Rowe et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%